Effectiveness of varmam therapy in kumbavatham periarthritis shoulder with special reference to restriction of Movements - MAANICKHA CHELVI K.S; RAJESH KUMAR; RAJENDRA KUMAR A. (International Journal of Pharma and Bio Sciences, 2016)
Siddha system is one of the traditional Indian system of medicine. It has a unique principles in the treatment of diseases according to pancha bootha theories which was developed into vali, azhal and iyyam. It is spiritually developed and its principles are based on self-realization of Siddhars. In this system of medicine, there are two types of therapies namely internal and external therapy. Both these types are classified into 32 subtypes. There are occasions where administration of oral medicines becomes impossible and hence to revive patient, administration of drugs other than oral routes and certain methods like varmam are highly efficacious. Varmam therapy can be used along with internal medications and external applications as well. Periarthritis shoulder, also called as adhesive capsulitis is one of the most common rheumatological problem in old age group especially, in diabetes mellitus subjects. It is the commonest long term complication next to osteoarthritis in Diabetes mellitus patients. Adhesive capsulitis or Periarthritis can be correlated with Kumbavatham which is one of the vatha diseases mentioned in the siddha literature Yugi Vaithya Chinthamani. The patients with Kumbavatham who underwent Varmam therapy in the OPD of SRRI, Puducherry were observed and results were presented. The effect of varmam therapy was assessed using Shoulder pain and disability (SPADI) index